Perbedaan Tingkat Kecemasan Ibu Hamil Trimester III Sebelum dan Sesudah Diberikan Prenatal Yoga - Ni Wayan Desi Suryaningsih; Regina Tedjasulaksana; Ni Luh Putu Sri Erawati (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Pregnancy is a natural condition in women that brings various physical, physiological, and psychological adaptations. Â If not properly managed, these psychological changes may trigger anxiety. Interviews with ten pregnant women in their third trimester indicated that seven of them (70%) often experienced anxiety. This research aimed to examine the difference in anxiety levels before and after participating in prenatal yoga among third-trimester pregnant women at UPTD Puskesmas IV South Denpasar. A quasi-experimental design with a one-group pretestâ€“posttest approach was used. The study took place from March to April 2024, employing simple random sampling and involving 24 respondents in their third trimester. Data were collected using questionnaires and analyzed through univariate analysis (frequency distribution) and bivariate analysis (normality test and Paired T-Test) with a significance value of p<0.05. Findings revealed a significant reduction in anxiety levels following prenatal yoga (p<0.000). Thus, prenatal yoga is recommended as an alternative strategy to help alleviate anxiety during pregnancy. Health professionals are encouraged to implement prenatal yoga as a non-pharmacological intervention, and further research is advised to consider additional variables that may contribute to anxiety.